Patient Satisfaction with Quality of Primary Care Health services‐findings from India. (2nd April 2022) - Persai, Divya; Balu, Ravi Kumar; Singh, Kalpana; Prabhu, Rajath R.; Lahoti, Supriya; Rout, Sarit; Panda, Rajmohan
Abstract: Background: Patient satisfaction is an essential indicator for measuring the quality of care. This study assessed patients' satisfaction with primary care services across different public health care system levels. Methods: The study was a cross‐sectional study conducted across three states in India. We adopted a multi‐stage stratified random sampling technique to select the districts(n‐13) and facilities (n‐55). A total of 4650 patients' exit interviews were conducted. Linear regression and analysis of variance was used to test the association. Analyses was performed using Stata software (version 15.0). Results: Patients visiting the primary facilities were more satisfied within the different domains of quality indicators that is, technical, communication, safety and cleanliness, and cost of services. The highest differences were observed on behaviour of other staff (Reg Coefficient 4.1 ± 0.8) and cleanliness of the ward (Reg Coefficient 4.0 ± 0.9). Significant negative association was observed in patient's satisfaction in the state of Kerala with an increase in age and education level. Conclusion: Our study suggests higher satisfaction at primary care facilities as compared to secondary and tertiary level facilities in the three states. Development of standardized tool and specific research on patient experience and its relation to the quality of care is needed in low‐ and middle‐income countries. Highlights: The satisfaction at primary care facilities was higher as compared to secondary and tertiary level facilities. The patients visiting the primary care facilities were satisfied on the quality indicators including technical, communication, safety and cleanliness, and cost of services. In the state of Kerala, significant negative association was observed in patient's satisfaction with increasing age and education level.